2015
DOI: 10.1002/chem.201502797
|View full text |Cite
|
Sign up to set email alerts
|

A General Access to Propargylic Ethers through Brønsted Acid Catalyzed Alkynylation of Acetals and Ketals with Trifluoroborates

Abstract: A general Brønsted acid catalyzed methodology for the alkynylation of acetals and ketals with alkynyltrifluoroborate salts has been developed. The reaction proceeds rapidly to afford valuable synthetic building block propargylic ethers in good to excellent yields. Unlike Lewis acid catalyzed transformations of trifluoroborates, this approach does not proceed via unstable organodifluoroborane intermediate. As a result, the developed methodology features excellent functional group tolerance and good atom economy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Previously, we discovered that tetrafluoroboric acid (HBF4) is an effective catalyst for the reactions of trifluoroborate salts [4,5]. To investigate the efficiency of the HBF4 as a Brønsted acidcatalyst towards the substitution of 2-ethoxytetrahydrofuran, we first looked at using unsubstituted potassium phenylacetylenetrifluoroborate salt (S1) as a model substrate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we discovered that tetrafluoroboric acid (HBF4) is an effective catalyst for the reactions of trifluoroborate salts [4,5]. To investigate the efficiency of the HBF4 as a Brønsted acidcatalyst towards the substitution of 2-ethoxytetrahydrofuran, we first looked at using unsubstituted potassium phenylacetylenetrifluoroborate salt (S1) as a model substrate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to use an alternative acid such as trifluoroacetic acid, which has a pK a similar to that of HBF 4 , only resulted in trace amounts of product formation (Table 1, entry 2). Our previous studies indicated that increasing the amounts of trifluoroborate salt and HBF 4¨O Et 2 to 1.5 equivalents resulted in a higher yield for the alkynylation of ketals [5]. We then looked to apply these reaction conditions to the direct functionalization of 2-ethoxytetrahydrofuran.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations